The rules of attraction in movie titles - Pastor, Lluís (Anàlisi, 2011)
This article explains an approach on the cognitive elements used in movie titles to persuade a local audience to watch a movie. The study focuses on the titles of foreign movies that have been modified in their translation into Spanish before they are exhibited in Spain. The theoretical framework used to carry out the research is based on Social Cognition. This theoretical trend, which resides halfway through social psychology and cognitive psychology, states that cognition over any communicative element can be done in two ways: the central or rational way and the peripheral or intuitive one. This study considers movie titles as persuasive elements that encourage a sort of peripheral cognition, thus the impact that they generate on the audience is fundamental. The article analyzes which are the mechanisms that said peripheral approach uses to attract the audiences to movie theaters through persuasion in the movie titles. The changes made in the titles of foreign movies that are released in Spain are analyzed in this sense.